Chlamydia trachomatis Infection Impairs MHC-I Intracellular Trafficking and Antigen Cross-Presentation by Dendritic Cells - Del Balzo, Diego; Capmany, Anahí; Cebrian, Ignacio; Damiani, María Teresa (Frontiers in Immunology, 2021)
During cross-presentation, exogenous antigens (i.e. intracellular pathogens or tumor cells) are internalized and processed within the endocytic system and also by the proteasome in the cytosol. Then, antigenic peptides are associated with Major Histocompatibility Complex (MHC) class I molecules and these complexes transit to the plasma membrane in order to trigger cytotoxic immune responses through the activation of CD8+ T lymphocytes. Dendritic cells (DCs) are particularly adapted to achieve efficient antigen cross-presentation and their endocytic network displays important roles during this process, including a sophisticated MHC-I transport dependent on recycling compartments. In this study, we show that C. trachomatis, an obligate intracellular pathogen that exhibits multiple strategies to evade the immune system, is able to induce productive infections in the murine DC line JAWS-II. Our results show that when C. trachomatis infects these cells, the bacteria-containing vacuole strongly recruits host cell recycling vesicles, but no other endosomal compartments. Furthermore, we found that chlamydial infection causes significant alterations of MHC-I trafficking in JAWS-II DCs: reduced levels of MHC-I expression at the cell surface, disruption of the perinuclear MHC-I intracellular pool, and impairment of MHC-I endocytic recycling to the plasma membrane. We observed that all these modifications lead to a hampered cross-presentation ability of soluble and particulate antigens by JAWS-II DCs and primary bone marrow-derived DCs. In summary, our findings provide substantial evidence that C. trachomatis hijacks the DC endocytic recycling system, causing detrimental changes on MHC-I intracellular transport, which are relevant for competent antigen cross-presentation.